GENERAL CHARACTERISTICS OF RAW MATERIALS FOR THE USE OF THE DEVELOPMENT OF BIOTECHNOLOGY FOR OBTAINING COMPLEX FERTILIZER (Eurasian Journal of Ecology, 2023)
Humic substances, formed as a result of the biotransformation of organic residues, are a natural product of the cooperative activities of ecosystem participants. To date, a huge amount of material has been accumulated in the study of the nature of soil HS, however, alternative sources of HS (peat, brown coal, oxidized coal, composts, etc.) have not been studied enough, therefore, comprehensive studies are needed for the use of these substances in agriculture and other areas. National economy. In Kazakhstan, there is an increasing shortage of organic fertilizers/ameliorants and there is a restriction on the use of chemical fertilizers and plant protection products. In this regard, it is reasonable to search for ways to use organic fertilizers of natural origin to increase soil fertility. Low-quality brown coal from local deposits can serve as a raw material for the production of HW. Coal-containing rocks possess a variety of essential chemical elements crucial for the advancement and nourishment of crops, making them a valuable source of nutrients within the soil. Introducing carbonaceous rocks into soddy-podzolic soils leads to a remarkable surge in microorganism population, often reaching several hundredfold. Utilizing carbonaceous rock amendments as soil fertilizers greatly enhances the activity of microbial communities engaged in the breakdown of organic constituents. Consequently, this process results in the enhancement of nutrient availability within the soil.The purpose of this stage of the study is to characterize the raw materials (humic substances isolated from low-quality brown coals of Kazakhstan deposits and bacterial cultures with high metabolic activity). As a result, a complete characterization of the raw material is given and active bacteria have been isolated and identified to use in the development of biotechnology for the production of complex fertilizer.Key words: brown coal, humic substances, technical characteristics, elemental composition, microbiome, metagenomics, bacterium.